Synthesis and crystal structures of 4,4′-methylenebis(2,6-diethylaniline) and 4,4′-methylenebis(3-chloro-2,6-diethylaniline) - Daniil E. Smirnov; Oleg S. Morozov; Ekaterina S. Afanasyeva; Viktor V. Avdeev (Acta Crystallographica Section E: Crystallographic Communications)
The title compounds 4,4′-methylenebis(2,6-diethylaniline) (C21H30N2, 1) and 4,4′-methylenebis(3-chloro-2,6-diethylaniline) (C21H28Cl2N2, 2) are of significant interest as curing agents for a wide range of resins and as building blocks for sterically demanding compounds in the synthesis of ligands for catalysis. This paper describes their synthesis and the preparation of single crystals, with their structures determined through single-crystal X-ray analysis. The presence of the chlorine substituent slightly affects the twist angle between the two aromatic components. The molecules of compound 1 form a network structure through intermolecular N—H...N bonds and C—H...π interactions, while in the crystal structure of compound 2, the molecules are assembled solely through N—H...π interactions. Consequently, despite their chemical similarity, it is the precise structural data that enables us to explain their differing reactivity and opens up the possibility of evaluating steric properties for the development of new materials and ligands.